A time series analysis of government expenditure and health outcomes in Nigeria - Bosede O. Awoyemi; Aderonke A. Makanju; Jane Mpapalika; Rita S. Ekpeyo (AOSIS, 2023)
Background: Despite a significant share of Nigeria's budget in the health sector, the health status has not improved, as reflected by poor health indicators. Objective: This study investigates the linkages between government expenditure and health outcomes in Nigeria. Methods: The Autoregressive Distributed Lag technique was used to examine the short- and long-run effects of government health expenditure on health outcomes separately. The health outcome was captured by life expectancy at birth and mortality rate. Results: Findings show a negative relationship exists between health expenditure and mortality rate, implying that a rise in health expenditure leads to a decrease in mortality rate, while life expectancy at birth positively responds to the changes in health expenditure. Conclusions: As a policy recommendation from this study, the government should pursue increasing health expenditure and partner with the private sector in the form of Public-Private Partnerships to improve the health sector and outcomes.